Pregnant outcomes of critically ill pregnant patients with pulmonary hypertension: A multicenter retrospective study - Zhang, Lin; Qie, Guoqiang; Yin, Xiaoyu; Zhao, Hongyan; Zhang, Fusen; Wang, Tao; Meng, Mei; Sha, Jing; Chu, Yufeng (Frontiers in Cardiovascular Medicine, 2022)
Objective: To identify the pregnancy outcomes and risk factors of critically ill pulmonary hypertension (PH) patients with intensive care unit (ICU) admission. Methods: The multi-centre, retrospective cohort study was performed on 60,306 parturients from January 2013 to December 2018 in China. Diagnosis of PH was based on the estimation of systolic pulmonary arterial pressure (sPAP) via echocardiography. Patients were stratified by sPAP into three groups, mild (30-50 mmHg), moderate (51-70 mmHg), and severe (>70 mmHg). The primary outcome was major adverse cardiovascular events (MACE), defined as a composite of in-hospital death, heart failure, sustained arrhythmias requiring treatment and embolic events. Secondary outcome was fetal adverse clinical events (FACE), a composite of fetal/neonatal death, prematurity, small birth weight and fetal distress. Results: A total of 181 pregnant patients were enrolled, including 101 patients with mild PH, 31 with moderate PH and 49 with severe PH. The maternal median age was 32 (27, 35) years and 37% were nulliparous. The MACE occurred in 59 (59/181, 32.6%) women, including in-hospital death in 13 (13/181, 7.2%), heart failure in 53 (53/181, 29.3%) and sustained arrhythmias in 7 (7/181, 3.9%). The incidence of FACE was as high as 66.3% (120/181). Compared with mild and moderate PH patients, patients with severe PH had a significantly higher mortality rate (22.4% versus 1.51%, P < 0.001) and MACE incidence (51.0% versus 25.8%, P=0.001). Although the incidence of FACE in severe PH was slightly higher than that in mild to moderate PH, there was no significant difference (69.4% versus 65.1%, P=0.724). PH complicated with left heart disease (OR=4.365, CI: 1.306-14.591), elevated N-terminal pro-B-type natriuretic peptide (NT-proBNP) level (OR=1.051, CI:1.015-1.088) and sPAP level estimated by echocardiography (OR=1.021; CI: 1.003-1.040) were independently associated with MACE in multivariable regression (P<0.05). Increased risk of FACE was noted for PH patients combined with eclampsia/preeclampsia (OR=6.713; CI: 1.806-24.959). Conclusion: The incidence of MACE and FACE remained high in critically ill pregnant patients with PH, particularly moderate and severe PH in China. Further studies are warranted to identify subsets of women with PH at lower pregnant risks, and seek more effective therapy to improve pregnancy outcomes.